Milk yield and milk composition responses to change in predicted net energy and metabolizable protein: a meta-analysis. (27th June 2016) - Daniel, J. B.; Friggens, N. C.; Chapoutot, P.; Van Laar, H.; Sauvant, D.
Abstract : Using a meta-analysis of literature data, this study aimed to quantify the dry matter (DM) intake response to changes in diet composition, and milk responses (yield, milk component yields and milk composition) to changes in dietary net energy for lactation (NEL ) and metabolizable protein (MP) in dairy cows. From all studies included in the database, 282 experiments (825 treatments) with experimentally induced changes in either NEL or MP content were kept for this analysis. These treatments covered a wide range of diet characteristics and therefore a large part of the plausible NEL and MP contents and supplies that can be expected in practical situations. The average MP and NEL contents were, respectively (mean±SD), 97±12 g/kg DM and 6.71±0.42 MJ/kg DM. On a daily supply basis, there were high between-experiment correlations for MP and NEL above maintenance. Therefore, supplies of MP and NEL above maintenance were, respectively, centred on MP supply for which MP efficiency into milk protein is 0.67, and NEL above maintenance supply for which the ratio of NEL milk/NEL above maintenance is 1.00 (centred variables were called MP67 and NEL100 ). The majority of the selected studies used groups of multiparous Holstein-Friesian cows in mid lactation, milked twice a day. Using a mixed model, between- and within-experiment variation was split to estimate DM intake and milk responses. The use of NEL100 and MP67 supplies substantially improved the accuracy of the prediction of milk yield and milk component yields responses with, on average, a 27% lower root mean square error (RMSE) relative to using dietary NEL and MP contents as predictors. For milk composition (g/kg), the average RMSE was only 3% lower on a supply basis compared with a concentration basis. Effects of NEL and MP supplies on milk yield and milk component yields responses were additive. Increasing NEL supply increases energy partitioning towards body reserve, whereas increasing MP supply increases the partition of energy towards milk. On a nitrogen basis, the marginal efficiency decreases with increasing MP supply from 0.34 at MP67 =−400 g/day to 0.07 at MP67 =300 g/day. This difference in MP67 supply, assuming reference energy level of NEL100 =0, equates to a global nitrogen efficiency decrease from 0.82 to 0.58. The equations accurately describe DM intake response to change in dietary contents and milk responses to change in dietary supply and content of NEL and MP across a wide range of dietary compositions.